500fold amplification of small molecule circularly polarized luminescence through circularly polarized FRET - Wade,J; Brandt,J; Reger,D; Zinna,F; Amsharov,K; Jux,N; Andrews,D; Fuchter,MJ (Angewandte Chemie International Edition, 2020)
Strongly dissymmetric circularly polarised (CP) luminescence from small organic molecules could transform a range of technologies, such as display devices. However, highly dissymmetric emission is usually not possible with small organic molecules, which typically give dissymmetric factors of photoluminescence ( g PL ) less than 10 2 . Here we describe an almost 10 3 fold chiroptical amplification of a πextended superhelicene when embedded in an achiral conjugated polymer matrix. This combination increases the |gPL| of the superhelicene from approximately 3 × 10 4 in solution to 0.15 in a blend film in the solidstate. We propose that the amplification arises not simply through a chiral environment effect, but instead due to electrodynamic coupling between the electric and magnetic transition dipoles of the polymer donor and superhelicene acceptor, and subsequent CP Förster resonance energy transfer. We show that this amplification effect holds across several achiral polymer hosts and thus represents a simple and versatile approach to enhance the gfactors of small organic molecules.